2006
DOI: 10.1111/j.1600-0722.2006.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative calcium binding of leucine‐rich amelogenin peptide and full‐length amelogenin

Abstract: Leucine-rich amelogenin peptide (LRAP) is an alternately spliced amelogenin. LRAP is known to bind to hydroxyapatite, and has been shown to signal mesenchymal cells to proliferate, but its function in enamel formation is unclear. The purpose of this study was to determine the calcium-binding properties and structure of recombinant human LRAP (rLRAP) compared with full-length amelogenin (rH174). rLRAP and rH174 were synthesized in Escherichia coli and purified by affinity chromatography and reverse-phase high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 26 publications
11
35
1
Order By: Relevance
“…Previously reported results based on using atomic absorption spectroscopy similarly indicated drops in Ca 2 + levels in rH174 sols but relatively constant phosphate levels therein during a set of constant composition experiments[13]. The initial drop in Ca 2 + levels corresponds well to the results of a study by Le et al[24], who reported sequestration of calcium ions by rH174 monomers, resulting in approximately 6 Ca 2 + ions bound to a single rH174 molecule.Hence 0.12 mM of Ca 2 + would be required to fully saturate rH174 molecules in concentration of 0.4 mg/ml rH174. This model explains the immediate drop from [Ca 2 + ]¼1.60 mM to [Ca 2 + ]¼1.47 mM following mixing of the given amount of CaCl 2 with 0.4 mg/ml rH174.…”
supporting
confidence: 77%
“…Previously reported results based on using atomic absorption spectroscopy similarly indicated drops in Ca 2 + levels in rH174 sols but relatively constant phosphate levels therein during a set of constant composition experiments[13]. The initial drop in Ca 2 + levels corresponds well to the results of a study by Le et al[24], who reported sequestration of calcium ions by rH174 monomers, resulting in approximately 6 Ca 2 + ions bound to a single rH174 molecule.Hence 0.12 mM of Ca 2 + would be required to fully saturate rH174 molecules in concentration of 0.4 mg/ml rH174. This model explains the immediate drop from [Ca 2 + ]¼1.60 mM to [Ca 2 + ]¼1.47 mM following mixing of the given amount of CaCl 2 with 0.4 mg/ml rH174.…”
supporting
confidence: 77%
“…However, experimental analyses do not always support the idea that the large middle portion of AMEL consists of a disordered structure, but instead suggest that this portion contains extended polyproline II and/or ␤ -spiral structures [Matsushima et al, 1998;Le et al, 2006;Margolis et al, 2006;Robinson, 2006]. Among milk/saliva/ enamel SCPPs, AMEL is especially rich in Pro and Gln, and has Pro-Xaa-Yaa repeats (Xaa and Yaa represent any amino acids but Pro and Gln appear frequently) within the C-terminal half.…”
Section: Disordered Protein and Skeletal Mineralizationmentioning
confidence: 95%
“…This enables them to regulate the shape and organisation of the calcium phosphate crystals during enamel mineralisation [184]. Combined with CD measurements, NMR analysis ( 1 H-15 N correlation spectroscopy) revealed a random coil structure for LRAP in aqueous solution at pH 4.0 and pH 7.5 [183]. Furthermore, CD spectroscopy and isothermal titration calorimetry showed that Ca 2+ ions interact with LRAP without inducing conformational changes of the protein.…”
Section: Liquid-state Nmr Of Biomolecules From Hydroxyapatite-based Bmentioning
confidence: 98%
“…Recently, another hydroxyapatite-binding biomolecule, leucinerich amelogenin peptide (LRAP), has been studied by NMR spectroscopy [183]. LRAP (5 kDa) is one of the amelogenin isoforms.…”
Section: Liquid-state Nmr Of Biomolecules From Hydroxyapatite-based Bmentioning
confidence: 99%